SYSTEMATIC LITERATURE REVIEW: HUBUNGAN SELF CONFIDENCE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Dilah Febriantini; Heni Pujiastuti; Aan Hendrayan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical problem-solving ability is a primary goal of mathematics education, but its success is highly influenced by affective factors, particularly self-confidence. This study aims to synthesize trends, distributions, relationship forms, methodological reviews, and intervention recommendations regarding the influence of self-confidence on middle school students’ mathematical problem-solving ability. The method used is a systematic literature review (SLR) following the PRISMA reporting guidelines. The literature search focused on the Google Scholar database, limiting the publication range from 2021 to early 2026. Through a rigorous selection process, 20 primary journal articles were identified as meeting the inclusion criteria and were data extracted. The synthesis results show that (1) publication trends are dominated in 2021–2022; (2) the majority of research focuses on junior high school students (75%) compared to senior high school students (25%); (3) the synthesis results indicate a consistent positive relationship between self-confidence and students’ mathematical problem-solving ability; (4) quantitative methodological approaches using Likert scale questionnaires predominantly measure affective variables; and (5) Problem-Based Learning (PBL) is the most recommended collaborative intervention model. These findings have important implications for integrating contextual approaches to reduce mathematical anxiety and recommend expanding observational research at the senior high school level.